Passive Smoking and Risk of Leukemia Among Children: A Casecontrol Study - Akter, Tanjila; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2025)
Background: Passive smoking is a significant public health concern, particularly in developing countries. This study aimed to investigate the association between passive smoking exposure and childhood leukemia in Bangladesh. Methods: A case-control study was conducted with 80 histopathologically confirmed leukemia cases and 80 agematched controls from three tertiary hospitals in Dhaka, Bangladesh. This case-control study was conducted among 160 participants (80 cases and 80 controls) from July 2019 to December 2019. Data were collected through face-to-face interviews and medical record reviews. Binary logistic regression analysis was performed to assess the association between passive smoking and childhood leukemia. Results: The median (IQR) age of cases was higher [8.0(4-12) years] than that of controls [6.0(9.5) years] and the majority of both groups (66.3% cases and 61.3% controls) were in the age group 1–10 years. Both groups had an equal gender distribution (62.5% male, 37.5% female). The prevalence of passive smoking exposure was higher among cases (82.5%) than in controls (55.0%). Children exposed to passive smoking had significantly higher odds of developing leukemia compared to those not exposed (AOR: 3.57, 95% CI: 1.65-7.72, p=0.001). Higher family income was also associated with increased odds of leukemia (AOR: 2.43, 95% CI: 1.16-5.10, p=0.019). More cases reported indoor exposure to passive smoking compared to controls (56.1% vs 84.1%, p=0.002). Maternal pesticide exposure during pregnancy was higher in cases than controls (25.0% vs 12.5%, p=0.043). Conclusion: Passive smoking exposure is significantly associated with childhood leukemia in Bangladesh. The study recommends strengthening. JOPSOM 2024; 43(1): 1-6